INTEGRASI SISTEM INFORMASI GEOGRAFIS (SIG) PARTICIPATORY DAN EVALUASI LOKASI TEKNIS UNTUK PERENCANAAN TATA RUANG WILAYAH DAN PERUMAHAN - Ginting, Adi Sabar; Lubis, Ruri Prihatini; Hidayat, Wahyu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study discusses two different approaches in the use of Geographic Information Systems (GIS) for regional spatial planning and housing location determination. The first study utilizes participatory GIS with multi-criteria decision-making method (MCDA) to increase public participation in spatial planning. Meanwhile, the second study applies GIS to determine the location of housing in Depok City based on spatial and technical data. This comparative study shows that both approaches have their own advantages: participatory GIS strengthens the inclusivity of decision-making, while technical GIS provides precision in site evaluation based on technical standards. The integration of these two approaches can result in a more holistic, efficient, and sustainable spatial planning model. The paper also recommends the development of a web-based GIS platform to incorporate inclusivity and precision of technical evaluation in spatial and housing planning.